Oxidized starch / zirconium halide perovskite nano-composite tanning agent as well as preparation method and application thereof

Through the preparation of oxidized starch/zirconium halogen perovskite nanocomposite composite tanning agent, the problem of surface over-tanning of zirconium tanning agent in leather tanning is solved, and a more uniform tanning effect and better leather-forming performance is achieved, which promotes leather making Green development of industry.

CN119193939AActive Publication Date: 2024-12-27SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411386717.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Zirconium tanning agent has surface overtanning during leather tanning, resulting in uneven distribution and limited performance.

Method used

The preparation method of oxidized starch/zirconium halogen perovskite nanocomposite composite tanning agent is adopted to generate zirconium halogen perovskite precursor by reaction of zirconium-based metal salt, cesium-based metal salt and acidic organic solvent, and corn starch and sodium periodate are added Afterwards, an oxidized starch/zirconium halogen perovskite is formed, and then combined with a zirconium salt tanning agent is formed, and a nano-composite tanning agent is formed by grinding and ball milling, which inhibits the hydrolysis of zirconium and improves the tanning performance.

Benefits of technology

It effectively slows down the hydrolysis of zirconium, improves the thickening rate and comfortable feel of the leather after tanning, enhances the thermal stability and filling properties of the leather, and promotes the greening process of the tanning industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193939A_ABST
    Figure CN119193939A_ABST
Patent Text Reader

Abstract

The invention discloses an oxidized starch / zirconium halide perovskite nano-composite tanning agent as well as a preparation method and application thereof, and belongs to the technical field of leather tanning agents. According to the preparation method disclosed by the invention, the adopted oxidized starch / zirconium halide perovskite is a nanocrystal composed of zirconium metal ions, cesium metal ions, chloride ions or bromide ions and oxidized starch, oleic acid and oleylamine as ligands, the zirconium ions and the oxidized starch can play a role in tanning, and in addition, the ligands can be used as a self-masking agent for inhibiting the hydrolysis of zirconium, so that the tanning effect is enhanced. The surface over-tanning phenomenon is relieved, the thickening rate of tanned crust leather is increased on the basis of realizing the zirconium tanned leather, and the crust leather is endowed with comfortable hand feeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of leather tanning agents, and specifically relates to an oxidized starch / zirconium halide perovskite nanocomposite tanning agent and a preparation method and application thereof. Background Art

[0002] The leather industry is an important livelihood industry closely related to agriculture, rural areas and farmers, and is a traditional pillar industry of light industry with international competitive advantages. Among them, tanning is the most critical process in leather making and is the qualitative change process of raw hides into leather. Chrome tanning is the most important and widely used tanning method in leather manufacturing. It gives crust leather excellent leather properties and currently occupies an absolute dominant position in the leather industry. However, in the traditional chrome tanning process, the absorption rate of chrome tanning agent is usually only about 70%, and high-concentration chromium-containing wastewater will be produced after tanning. This not only increases the environmental pollution load and wastewater treatment costs, but also causes great waste of resources. Compared with traditional chrome-tanned leather, the production process of chrome-free leather is cleaner and more environmentally friendly. Therefore, it is imperative to promote the green development of the leather industry and chrome-free tanning. Zirconium tanning agent has a similar tanning effect to chrome tanning agent and is considered to be an ideal substitute for chrome tanning agent. Zirconium-tanned leather has a firm grain surface and good filling and wear resistance, but the leather is hard. The strong hydrolysis and polymerization of zirconium salts causes it to deposit on the leather surface and distribute unevenly, resulting in surface over-tanning, which limits the application of zirconium tanning agents. Starch is a natural polysaccharide biomass material with a wide range of sources and is renewable. After modification, functional groups such as aldehydes and carboxyls are introduced, which can produce relatively strong cross-linking with skin collagen and have certain tanning properties. However, the degree of cross-linking between a single starch tanning agent and skin collagen is insufficient and still needs to be used in conjunction with metal salts. Summary of the invention

[0003] The purpose of the present invention is to provide an oxidized starch / zirconium halide perovskite nanocomposite tanning agent and a preparation method and application thereof, so as to solve the technical problem of surface over-tanning when the zirconium tanning agent is used.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent, comprising the following steps: A zirconium-based metal salt, a cesium-based metal salt and an acidic organic solvent are mixed and placed in a water bath container for heating reaction to obtain a product; oleic acid and oleylamine ligands are added to the product for reaction, and a zirconium halide perovskite precursor solution is obtained after the reaction is completed; Adding corn starch, sodium periodate and an acidic solution to a zirconium halide perovskite precursor solution, heating the solution for reaction, and then post-treating the obtained product to obtain oxidized starch / zirconium halide perovskite; The oxidized starch / zirconium halide perovskite is compounded with a zirconium salt tanning agent to obtain an oxidized starch / zirconium halide perovskite nanocomposite tanning agent.

[0005] Furthermore, the temperature for the heating reaction in the water bath container is 30-60°C, and the time is 30-90 minutes; magnetic stirring is used when the heating reaction is placed in the water bath container; and the time for adding oleic acid and oleylamine ligands to the product to react is 10-50 minutes.

[0006] Furthermore, the zirconium-based metal salt is one of zirconium chloride or zirconium bromide; the cesium-based metal salt is cesium chloride or cesium bromide; the acidic organic solvent is obtained by mixing an acidic solute and a solvent; the solvent is hexadecene or octadecene; the acidic solute is one of formic acid and lactic acid; and the pH of the acidic organic solvent is 1 to 3.

[0007] Furthermore, the mass volume ratio of the zirconium-based metal salt, the cesium-based metal salt, the solvent and the acidic solute is 2g:1g:(2-6)mL:(40-60)mL.

[0008] Furthermore, the mass volume ratio of the zirconium-based metal salt, oleic acid and oleylamine is 1 g:2 mL:(6-12 mL).

[0009] Furthermore, when preparing oxidized starch / zirconium halide perovskite, the temperature of the heating reaction is 38-45° C., and the time is 30-90 min; magnetic stirring is performed during the heating reaction, and the magnetic stirring speed is 30-800 r / min.

[0010] Furthermore, the mass ratio of the zirconium-based metal salt, corn starch and sodium periodate is (2-6): (1-2): (2-3); the amount of the acidic solution added is until the pH of the solution is 2-3; The post-treatment includes centrifugation, washing and drying; the time of the centrifugation is 8 to 40 minutes; the washing is performed 1 to 4 times with a non-polar solvent; the non-polar washing solvent is chloroform or n-hexane.

[0011] Furthermore, the mass ratio of the oxidized starch / zirconium halide perovskite to the zirconium salt tanning agent is 1:2 to 2:1; the zirconium salt tanning agent is zirconium sulfate, zirconium chloride or zirconium oxychloride; The compounding is achieved by grinding and ball milling for 30 to 240 minutes.

[0012] The invention also discloses an oxidized starch / zirconium halide perovskite nano composite tanning agent prepared by the preparation method.

[0013] The present invention also discloses the use of the above-mentioned oxidized starch / zirconium halide perovskite nanocomposite tanning agent in leather tanning, comprising the following steps: Add acid leather and water in a mass ratio of 1:1-1:3 into a drum, then add 8%-10% of the mass of the acid leather with sodium chloride and 10% acetic acid solution, adjust the bath liquid to pH 1.0-3.5 for the first time, and rotate for 60 min; add 3%-15% of the mass of the acid leather with oxidized starch / zirconium halide perovskite nanocomposite tanning agent to the bath liquid, and rotate for 3-10 h; then adjust the bath liquid pH to 5.5-9.0 for the second time with 10% sodium bicarbonate solution, and rotate for 45 min; heat to 35-40℃, rotate for 3 h, let stand for 12 h, rotate for another 60 min, and wash with water.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent. The oxidized starch / zirconium halide perovskite used is a nanocrystal composed of zirconium metal ions, cesium metal ions, chloride ions or bromide ions with oxidized starch, oleic acid and oleylamine as ligands. The zirconium ions and oxidized starch can play a tanning role. In addition, the ligands can be used as self-masking agents to inhibit the hydrolysis of zirconium and slow down the over-tanning phenomenon on the surface. On the basis of achieving zirconium tanned leather, the thickening rate of the tanned leather is improved and the leather is given a comfortable hand feel.

[0015] Furthermore, the method disclosed in the present invention adopts a one-pot method to prepare oxidized starch / zirconium halide perovskite nano-composite tanning agent, which is simple to operate and easy to repeat. When applied to leather tanning, it can give the raw leather excellent thermal stability, comfortable feel, good filling properties, etc., which is conducive to promoting the green process of the leather industry.

[0016] The present invention also discloses an oxidized starch / zirconium halide perovskite nanocomposite tanning agent prepared by the above-mentioned preparation method. In the present invention, the oxidized starch / zirconium halide perovskite and the metal salt tanning agent can realize efficient synergistic tanning; the presence of the metal salt tanning agent can not only play a tanning role, but also inhibit the hydrolysis of the perovskite, maintain the perovskite nanocrystalline structure, so that the tanning agent can better penetrate into the leather fiber, and further improve the leather performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a comparison chart of the shrinkage temperature and thickening rate of the crust leather after tanning and the crust leather after zirconium sulfate tanning when the oxidized starch / zirconium halide perovskite nano-composite tanning agent is applied to sheepskin tanning in Example 2. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0023] The present invention provides a method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent, comprising the following steps: Step 1, preparing a zirconium halide perovskite precursor solution: adding a zirconium-based metal salt and a cesium-based metal salt into a flask containing an acidic organic solvent, heating in a water bath at 30-60°C, stirring with a magnetic force, reacting for 30-90 minutes to obtain a uniform and transparent solution, then adding oleic acid and oleylamine ligands, reacting for 10-50 minutes, and obtaining a white turbid zirconium halide perovskite precursor solution; Step 2, preparing oxidized starch / zirconium halide perovskite: adding corn starch, sodium periodate and a small amount of acidic solution to the precursor solution of step 1, heating in a water bath at 38-45°C, stirring with a magnetic force, reacting for 30-90 minutes, stopping heating and stirring, cooling the product and centrifuging for 8-40 minutes, taking the bottom precipitate, washing it with a non-polar solvent for 1-4 times, and drying it at room temperature to obtain oxidized starch / zirconium halide perovskite; Step 3, preparation of oxidized starch / zirconium halide perovskite nanocomposite tanning agent: compound the oxidized starch / zirconium halide perovskite in step 2 with the zirconium salt tanning agent, and obtain an oxidized starch / zirconium halide perovskite nanocomposite tanning agent after 30 to 240 minutes of compounding by means of grinding and ball milling.

[0024] The present invention also discloses the use of the above-mentioned oxidized starch / zirconium halide perovskite nanocomposite tanning agent in leather tanning, comprising the following steps: Add acid leather and water in a mass ratio of 1:1-1:3 into a drum, then add 8%-10% of the mass of the acid leather with sodium chloride and 10% acetic acid solution, adjust the bath liquid to pH 1.0-3.5 for the first time, and rotate for 60 min; add 3%-15% of the mass of the acid leather with oxidized starch / zirconium halide perovskite nanocomposite tanning agent to the bath liquid, and rotate for 3-10 h; then adjust the bath liquid pH to 5.5-9.0 for the second time with 10% sodium bicarbonate solution, and rotate for 45 min; heat to 35-40℃, rotate for 3h, let stand overnight, rotate for 60min the next day, and wash with water.

[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0026] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0027] Example 1 A method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent comprises the following steps: 800 mg of zirconium bromide and 400 mg of cesium bromide were added to a flask containing formic acid and hexadecene, heated in a water bath at 30°C and stirred magnetically for 30 minutes to obtain a uniform and transparent solution, and then oleic acid and oleylamine ligands were added and reacted for 20 minutes to obtain a white turbid zirconium halide perovskite precursor solution. The mass volume ratio of zirconium bromide, cesium bromide, formic acid, hexadecene, oleic acid, and oleylamine was 2 g: 1 g: 2 mL: 30 mL: 4 mL: 12 mL. Add 400 mg corn starch, 800 mg sodium periodate and a small amount of dilute hydrochloric acid with a pH of 2 to the zirconium halide perovskite precursor solution, heat in a water bath at 38°C, stir magnetically, react for 30 minutes, stop heating and stirring, cool the product and centrifuge for 15 minutes, take the bottom precipitate, wash with n-hexane twice, and dry at room temperature to obtain oxidized starch / zirconium halide perovskite; Oxidized starch / zirconium halide perovskite is compounded with zirconium chloride and ground for 30 minutes to obtain an oxidized starch / zirconium halide perovskite nanocomposite tanning agent, wherein the mass ratio of the oxidized starch / zirconium halide perovskite to the zirconium salt tanning agent is 1:1.

[0028] Example 2 A method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent comprises the following steps: 600 mg of zirconium chloride and 300 mg of cesium chloride were added to a flask containing formic acid and octadecene, heated in a water bath at 45°C and stirred magnetically for 30 minutes to obtain a uniform and transparent solution, and then oleic acid and oleylamine ligands were added and reacted for 60 minutes to obtain a white turbid zirconium halide perovskite precursor solution. The mass volume ratio of zirconium chloride, cesium chloride, formic acid, octadecene, oleic acid and oleylamine was 2 g: 1 g: 4 mL: 60 mL: 4 mL: 16 mL; 200 mg corn starch, 300 mg sodium periodate and a small amount of dilute hydrochloric acid with a pH of 2 were added to the zirconium halide perovskite precursor solution, heated in a water bath at 40°C and stirred magnetically, reacted for 60 minutes, then the heating and stirring were stopped, the product was cooled and centrifuged for 20 minutes, the bottom precipitate was taken, washed with chloroform three times, and dried at room temperature to obtain oxidized starch / zirconium halide perovskite; Oxidized starch / zirconium halide perovskite is compounded with zirconium chloride, and after grinding and compounding for 30 minutes, an oxidized starch / zirconium halide perovskite nanocomposite tanning agent is obtained, wherein the mass ratio of the oxidized starch / zirconium halide perovskite to the zirconium salt tanning agent is 2:1.

[0029] Example 3 A method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent comprises the following steps: 400 mg of zirconium chloride and 200 mg of cesium chloride were added to a flask containing lactic acid and hexadecene, heated in a water bath at 60°C and stirred magnetically for 90 minutes to obtain a uniform and transparent solution, and then oleic acid and oleylamine ligands were added and reacted for 40 minutes to obtain a white turbid zirconium halide perovskite precursor solution. The mass volume ratio of zirconium chloride, cesium chloride, formic acid, hexadecene, oleic acid and oleylamine was 2 g: 1 g: 6 mL: 90 mL: 4 mL: 20 mL. 150 mg corn starch, 300 mg sodium periodate and a small amount of dilute sulfuric acid with a pH of 3 were added to the zirconium halide perovskite precursor solution, heated in a water bath at 45°C and magnetically stirred, and reacted for 90 minutes, then the heating and stirring were stopped, the product was cooled and centrifuged for 30 minutes, the bottom precipitate was taken, and washed with n-hexane for 4 times, and dried at room temperature to obtain oxidized starch / zirconium halide perovskite; Oxidized starch / zirconium halide perovskite is compounded with zirconium chloride, and after grinding and compounding for 60 minutes, an oxidized starch / zirconium halide perovskite nanocomposite tanning agent is obtained, wherein the mass ratio of the oxidized starch / zirconium halide perovskite to the zirconium salt tanning agent is 1:1.

[0030] Example 4 A method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent comprises the following steps: 400 mg of zirconium chloride and 200 mg of cesium chloride were added to a flask containing lactic acid and hexadecene, heated in a water bath at 60°C and stirred magnetically for 90 minutes to obtain a uniform and transparent solution, and then oleic acid and oleylamine ligands were added and reacted for 40 minutes to obtain a white turbid zirconium halide perovskite precursor solution. The mass volume ratio of zirconium chloride, cesium chloride, hexadecene, formic acid, lactic acid, oleic acid and oleylamine was 2 g: 1 g: 2 mL: 40 mL: 4 mL: 24 mL. 150 mg corn starch, 300 mg sodium periodate and a small amount of dilute sulfuric acid with a pH of 3 were added to the zirconium halide perovskite precursor solution, heated in a water bath at 38°C and magnetically stirred, reacted for 90 minutes, then the heating and stirring were stopped, the product was cooled and centrifuged for 30 minutes, the bottom precipitate was taken, and washed with n-hexane for 4 times, and dried at room temperature to obtain oxidized starch / zirconium halide perovskite; Oxidized starch / zirconium halide perovskite is compounded with zirconium chloride, and after grinding and compounding for 60 minutes, an oxidized starch / zirconium halide perovskite nanocomposite tanning agent is obtained, wherein the mass ratio of the oxidized starch / zirconium halide perovskite to the zirconium salt tanning agent is 2:1.

[0031] Application Example 1 The oxidized starch / zirconium halide perovskite nanocomposite tanning agent prepared in Example 1 is used for leather tanning, comprising the following steps: Add acid leather and water in a mass ratio of 1:1 into a rotating drum, then add sodium chloride (9% by mass of the acid leather) and acetic acid solution (10% by concentration), adjust the bath liquid to pH 2.5 for the first time, and rotate for 60 min; add oxidized starch / zirconium halide perovskite nanocomposite tanning agent (5% by mass of the acid leather) to the bath liquid, and rotate for 4 h; then adjust the bath liquid pH to 6.0 for the second time with sodium bicarbonate solution (10% by concentration), and rotate for 45 min; heat to 35°C, rotate for 3 h, let stand overnight, rotate for 60 min the next day, and wash with water.

[0032] Application Example 2 The oxidized starch / zirconium halide perovskite nanocomposite tanning agent prepared in Example 2 is used for leather tanning, comprising the following steps: Add acid leather and water in a mass ratio of 1:2 into a rotating drum, then add 9% sodium chloride by mass of the acid leather and 10% acetic acid solution, adjust the bath liquid to pH 3.0 for the first time, and rotate for 60 min; add 10% oxidized starch / zirconium halide perovskite nanocomposite tanning agent by mass of the acid leather to the bath liquid, and rotate for 6 h; then adjust the bath liquid pH to 7.0 for the second time with 10% sodium bicarbonate solution, and rotate for 45 min; heat to 35°C, rotate for 3 h, let stand overnight, rotate for 60 min the next day, and wash with water.

[0033] Application Example 3 The oxidized starch / zirconium halide perovskite nanocomposite tanning agent prepared in Example 3 is used for leather tanning, comprising the following steps: Add acid leather and water in a mass ratio of 1:3 into a drum, then add sodium chloride (9% by mass of the acid leather) and acetic acid solution (10% by concentration), adjust the bath liquid to pH 3.0 for the first time, and rotate for 60 min; add oxidized starch / zirconium halide perovskite nanocomposite tanning agent (15% by mass of the acid leather) to the bath liquid, and rotate for 10 h; then adjust the bath liquid pH to 8.0 for the second time with sodium bicarbonate solution (10% by concentration), and rotate for 45 min; heat to 40°C, rotate for 3 h, let stand overnight, rotate for 60 min the next day, and wash with water.

[0034] Oxidized starch / zirconium halide perovskite has an ionic structure. Zirconium ions and oxidized starch with excellent tanning functions are introduced into the perovskite structure to make it a high-efficiency leather tanning agent. By compounding it with a zirconium salt tanning agent, an oxidized starch / zirconium halide perovskite nanocomposite tanning agent can be obtained, which further improves the water resistance stability of the perovskite and the tanning properties of the tanning agent.

[0035] Figure 1 The following is a comparison chart of the shrinkage temperature and thickening rate of the crust leather after tanning and the crust leather after tanning with zirconium sulfate in Example 2, where the oxidized starch / zirconium halide perovskite nanocomposite tanning agent is applied to sheepskin tanning. It can be seen from the figure that the crust leather after tanning with the oxidized starch / zirconium halide perovskite nanocomposite tanning agent has the highest shrinkage temperature and good thickening rate, indicating that it has the best moisture and heat resistance stability and a fuller feel.

[0036] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent, characterized in that: The following steps are involved: A zirconium-based metal salt, a cesium-based metal salt and an acidic organic solvent are mixed and placed in a water bath container for heating reaction to obtain a product; Adding oleic acid and oleylamine ligand to the product for reaction, and obtaining a zirconium halide perovskite precursor solution after the reaction is completed; Adding corn starch, sodium periodate and an acidic solution to a zirconium halide perovskite precursor solution, heating the solution for reaction, and then post-treating the obtained product to obtain oxidized starch / zirconium halide perovskite; The oxidized starch / zirconium halide perovskite is compounded with a zirconium salt tanning agent to obtain an oxidized starch / zirconium halide perovskite nanocomposite tanning agent.

2. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 1, characterized in that: The temperature for the heating reaction in the water bath container is 30-60°C, and the time is 30-90 min. Magnetic stirring is used when the heating reaction is carried out in the water bath container. The time for adding oleic acid and oleylamine ligands to the product to react is 10-50 min.

3. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 1, characterized in that: The zirconium-based metal salt is one of zirconium chloride and zirconium bromide; the cesium-based metal salt is cesium chloride or cesium bromide; the acidic organic solvent is obtained by mixing an acidic solute and a solvent; the solvent is hexadecene or octadecene; the acidic solute is one of formic acid and lactic acid; and the pH of the acidic organic solvent is 1 to 3.

4. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 3, characterized in that: The mass volume ratio of the zirconium-based metal salt, the cesium-based metal salt, the solvent and the acidic solute is 2g:1g:(2-6)mL:(40-60)mL.

5. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 1, characterized in that: The mass volume ratio of the zirconium-based metal salt, oleic acid and oleylamine is 1 g:2 mL:(6-12 mL).

6. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 1, characterized in that: When preparing oxidized starch / zirconium halide perovskite, the temperature of the heating reaction is 38-45° C., and the time is 30-90 min. During the heating reaction, magnetic stirring is performed, and the magnetic stirring speed is 30-800 r / min.

7. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 1, characterized in that: The mass ratio of the zirconium-based metal salt, corn starch and sodium periodate is (2-6): (1-2): (2-3); the amount of the acidic solution added is until the pH value of the solution is 2-3; The post-treatment includes centrifugation, washing and drying; The centrifugal treatment time is 8 to 40 minutes; the washing is performed by washing with a non-polar solvent for 1 to 4 times; and the non-polar washing solvent is chloroform or n-hexane.

8. The method for preparing an oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 1, characterized in that: The mass ratio of the oxidized starch / zirconium halide perovskite to the zirconium salt tanning agent is 1:2 to 2:1; the zirconium salt tanning agent is zirconium sulfate, zirconium chloride or zirconium oxychloride; The compounding is achieved by grinding and ball milling for 30 to 240 minutes.

9. An oxidized starch / zirconium halide perovskite nanocomposite tanning agent, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the oxidized starch / zirconium halide perovskite nanocomposite tanning agent according to claim 9 in leather tanning, characterized in that: The following steps are involved: Add acid leather and water in a mass ratio of 1:1-1:3 into a drum, then add 8%-10% of the mass of the acid leather with sodium chloride and 10% acetic acid solution, adjust the bath liquid to pH 1.0-3.5 for the first time, and rotate for 60 min; add 3%-15% of the mass of the acid leather with oxidized starch / zirconium halide perovskite nanocomposite tanning agent to the bath liquid, and rotate for 3-10 h; then adjust the bath liquid pH to 5.5-9.0 for the second time with 10% sodium bicarbonate solution, and rotate for 45 min; heat to 35-40℃, rotate for 3 h, let stand for 12 h, rotate for another 60 min, and wash with water.

Citation Information

Patent Citations

  • Preparation method of starch-based green leather tanning agent

    CN101880334A

  • Carboxylic acid ligand MOFs nano tanning agent with stable frame structure as well as preparation method and application of carboxylic acid ligand MOFs nano tanning agent

    CN113073160A

  • Self-masking type zirconium-based halide perovskite nano tanning agent and preparation method thereof

    CN115627302A

  • Light-color multi-carboxyl oxidized polysaccharide tanning agent, and preparation method therefor and use thereof

    WO2022166201A1